Self‐concept but not prior knowledge moderates effects of different implementations of computer‐assisted inquiry learning activities on students' learning. (5th April 2022) - Richter, Juliane; Lachner, Andreas; Jacob, Leonie; Bilgenroth, Friederike; Scheiter, Katharina
Abstract: Background: Engaging students in computer‐assisted guided inquiry learning has great potential to scaffold their scientific understanding: Students are expected to improve their scientific problem‐solving skills, and at the same time gain a deep conceptual understanding of the subject‐matter. Additional generative activities such as creating video explanations subsequent to inquiry learning activities can also further deepen students' knowledge. Objectives: In this experiment, we therefore compared the effectiveness of computer‐based direct instruction (to mimic traditional classroom teaching) versus computer‐based inquiry learning. Methods: University students ( N = 118) either received video‐based direct instruction (direct instruction), including the demonstration of a virtual experiment, or conducted the virtual experiment themselves supported by prompts (inquiry learning). A third group of students additionally generated a video explanation as consolidation activity subsequent to conducting the virtual experiment (inquiry learning + generative activity). Results and Conclusions: Contrarily to our hypotheses, the direct instruction condition outperformed the inquiry learning conditions. There were no significant differences between the inquiry learning and the inquiry learning + generative activity condition. Moderation analyses revealed that the effectiveness of direct instruction predominantly held true for students with low levels of domain‐specific self‐concept. All in all, our present study contributes to a better understanding of effects of direct instruction versus guided inquiry learning in computer‐based science education settings. Importantly, our findings show that the effectiveness of instructional approaches may depend on students' domain‐specific self‐concept as a motivational prerequisite. As such it is up for further research in science education to identify motivating instructional strategies to enhance students' learning. Lay Description: What is already known about this topic: Computer‐assisted guided inquiry learning has great potential to scaffold students' scientific understanding. However, inquiry learning can be cognitively overwhelming, particularly for novice students. Direct instruction is frequently discussed as an alternative to inquiry learning, as students are explicitly taught on the subject‐matter content. What this paper adds: We investigated (a) the effectiveness of three different computer‐based instructional approaches including inquiry learning and direct instruction and (b) the role of students' cognitive and motivational prerequisites. Contrary to our hypotheses, students in the guided inquiry conditions did not outperform those in the direct instruction condition. Moreover, especially students with a low domain‐specific self‐concept profited from direct instruction compared to inquiry learning. Implications for practice and/or policy: All in all, our present study contributes to a better understanding of effects of direct instruction versus guided inquiry learning in computer‐based science education settings. Importantly, our findings show that the effectiveness of instructional approaches may depend on students' domain‐specific self‐concept as a motivational prerequisite. As such it is up for further research in science education to identify motivating instructional strategies to enhance students' learning.